Given:
![cos\text{ }s=(1)/(5);sin\text{ }t=(4)/(5)](https://img.qammunity.org/2023/formulas/mathematics/college/5ob8mrcvsz52k6xfq21iap08df0bherwi5.png)
We will find cos (s+t) and cos (s-t)
First, we need to find the sin (s) and cos (t) using the trigonometric Pythagorean identity: sin²x + cos²x = 1
So,
![\begin{gathered} sin\text{ }s=√(1-cos^2s)=(√(24))/(5) \\ \\ cos\text{ }t=√(1-sin^2t)=(3)/(5) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/5mrbcy102qdki58fytosm2m5v9sozhhpcw.png)
Second, we will find cos(s+t) using the difference identity as follows:
![cos(s+t)=cos\text{ }s*cos\text{ }t-sin\text{ }s*sin\text{ }t](https://img.qammunity.org/2023/formulas/mathematics/college/b00nogw74vmya9vwz5e1pyuxvkbxa3nrf5.png)
Substitute with the values of the sine and cosine of both angles.
![cos(s+t)=(1)/(5)*(3)/(5)-(√(24))/(5)*(4)/(5)=(3)/(25)-(4√(24))/(25)=(3-8√(6))/(25)](https://img.qammunity.org/2023/formulas/mathematics/college/51mk1nfmaqb4eyemgyco4v8m9jwc6awo38.png)
Finally, we will find cos (s - t)
![cos(s-t)=cos\text{ }s*cos\text{ }t+sin\text{ }s*sin\text{ }t](https://img.qammunity.org/2023/formulas/mathematics/college/1gd00z1tk4ghsckvpxbaj8r9b56w6s5hj4.png)
Substitute with the values of the sine and cosine of both angles.
![cos(s-t)=(1)/(5)*(3)/(5)+(√(24))/(5)*(4)/(5)=(3)/(25)+(8√(6))/(25)=(3+8√(6))/(25)](https://img.qammunity.org/2023/formulas/mathematics/college/sxlxr75t00nklrcaxapbfjcg7b7od740xe.png)
So, the answer will be:
![\begin{gathered} cos(s+t)=(3-8√(6))/(25) \\ \\ cos(s-t)=(3+8√(6))/(25) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/k35c3a0h3tcr8d6tnq9hpu4mpnwo5s2air.png)